Clinical profile of geriatric cervical cancer patients in a tertiary hospital in Surabaya, Indonesia - Natasya Dyah Ayu Purnamasari; Brahmana Askandar Tjokroprawiro; Budi Utomo; Nila Kurniasari (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Squamous cell carcinoma majorly covered in histopathologic of the records, while adenosquamous followed second. Most of the subjects were referral patients to Dr. Soetomo General Academic Hospital. They were mostly originated from Java outside Surabaya.   ABSTRACT Objective: To identify the distribution of age, histopathology type, clinical stage, treatment type, parity, first complaint, and referral origin of geriatric cervical cancer patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Materials and Methods: This study was a retrospective study observing data from medical records and presented the data descriptively. The medical records were taken from Oncology Outpatient Clinic in Dr. Soetomo Hospital, from 2020-2021, covering geriatric patients aged more than 55 years old. The data were screened and processed. Results: At Dr. Soetomo Hospital, in 2020-2021 there were 228 cervical cancer patients. From 176 patient data that met the inclusion criteria, the average age was 65.38 ± 4.86 years, with 4 types of histopathology dominated by squamous cell carcinoma (82.39%), adenocarcinoma (11.93%), adenoquamous (3.41%) and others (4%), divided into 8 clinical stages and dominated by stages IIIB (77.27%), IIB (15.9%), IVB (2.84%), IIIA and IB had same number (1.14%), 1A (0.57%) and no cases of IIA were found. The treatments were dominated by chemotherapy (86.36%), radiation therapy (7.38%), no treatment (3.41%), hysterectomy (1.7%), while for conization and palliative therapy each in 1 case (0.57%). Most experienced 3 parity (29.5%), followed by 4 parity (17.61%), >5 (13.07%), 5 (10.23%), 1 (6.82%) and no parity (2.27%). The three first complaints were. vaginal bleeding (82.38%), vaginal discharge (46.02%), and pain (82.38%), and the patients were dominated by referrals from Java Island other than Surabaya City (78.40%), outside Surabaya in Java Island as many as 36 referrals (20.45%) and outside Java Island 2 referrals (1.14%). Conclusion: There were 176 geriatric patients with cervical cancer at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in the 2020-2021 period, dominated by age 56-65 years, the histopathology type of squamous cell carcinoma, stage IIIB patients, most received therapy was chemotherapy, most were multiparous with 3 parities, the majority experienced complaints of vaginal bleeding when diagnosed with cervical cancer, and were dominated by referrals from Java Island outside Surabaya.